The Socialization of Spouses and Its Reflections on Children's Psychological and Social Health -Background and Dimensions- - Teyb, Boulanouar; Dhib, Mohammed (Journal of Ecohumanism, 2026)
Positive levels of psychological and social health among children can be reached when several factors are present. These factors give strength to a central social act. Its purpose is to preserve the human element and to maintain its role in society.Marriage, in its traditional meaning, is a conscious process. It shapes the behaviour of children from an early age. It also prepares them to assume responsibilities and to understand what is expected of them within the social group to which they belong.Society is a system of relations and functions. Each individual is therefore expected to maintain the social structure and to activate the dynamics of its human components. In social custom, marriage becomes a conscious traditional act. It is based on foundations inherited across generations through the practice of choice.This choice may rest on compatibility. It may also be more realistic, especially when adults have information about the potential partner with whom they intend to share their life. The growth of emotional and daily-life needs pushes individuals to seek independence from the family of origin. It may also persuade them to comply with social custom, to understand the traits of the other partner, and to expect a dignified life with them.In this sense, marriage aims to build a family that preserves family lineage. It also transmits the values of society from one generation to another. Socialization institutions must prepare future spouses before marriage. They must introduce them to the principles and rules of marital life.This tradition is a survival strategy. It seeks to repair the social structure and to support the continuity of social life. Within the family environment, practices emerge in which each spouse performs duties toward the other before demanding rights. This may make the whole family, especially children, more psychologically balanced and more socially harmonious.